TREATING INFERTILITY BY CHINESE HERBS - J, Nagendra; S, Jayachandra (Journal of Postgraduate Medical Institute, 2011)
The World Health Organization (WHO) estimates that approximately 8-10% of couples experience some form of infertility problem. On a worldwide scale, this means that 50-80 million people suffer from infertility. However, the incidence of infertility may vary from region to region .